Talking Stagnation: Thematic Analysis of Terrorism Experts’ Perception of the Health of Terrorism Research - Morrison, John F. (Terrorism and political violence, 2022)
In 2014, Marc Sageman proposed that terrorism research had stagnated. The claim of stagnation has resulted in a period of collective review within terrorism studies. To date, the fruits of this review have revealed a more cautiously optimistic view of the field than that proposed by Sageman. This article aims to add to this review by analyzing the interviews of forty-three guests from the first season of the Talking Terror podcast. Presented is a thematic analysis of their views on the overall health of terrorism research. The interviewees included both pre-and post-9/11 researchers. Through this analysis four themes are identified: Interdisciplinary Research and Researchers, Data, Applied Research, and Area/Field. The majority of interviewees were more optimistic than Sageman in relation to the overall health of the area. Analysis of their responses is presented alongside some recommendations for the future direction of the area.